Feasibility and Efficacy of an Isocaloric High-Protein vs. Standard Diet on Insulin Requirement, Body Weight and Metabolic Parameters in Patients with Type 2 Diabetes on Insulin Therapy - Luger, M.; Holstein, B.; Schindler, K.; Kruschitz, R.; Ludvik, B. (Experimental and Clinical Endocrinology & Diabetes, 2013)
To determine the feasibility and efficacy of a high-protein diet compared with a standard diet aiming for weight maintenance in insulin treated type-2 diabetic patients on insulin requirement, body weight and metabolic parameters over 12 weeks.In a randomized controlled trial we assigned 44 type-2 diabetic patients on insulin therapy either to high-protein or standard diet over 12 weeks. Parameters were evaluated at baseline and monthly.After 12 weeks, the high protein diet significantly decreased insulin requirement (9.4±16.3 vs. +0.8±4.8 IU, mean±SD; p=0.007), fasting plasma glucose (41.7±62.5 vs. 2.1±39.0 mg dl− 1; p=0.02), body mass index (1.1±0.8 vs. 0.3±0.7 kg m− 2; p=0.003), fat-free (0.8±0.5 vs. 0.2±0.5kg; p=0.001), fat mass (2.6±1.7 vs. 0.8±1.6kg; p=0.001) and increased serum folate (4.2±8.3 vs. − 0.8±5.5 nmol l−1; p=0.04) compared to the standard diet. These beneficial metabolic effects are most likely related to the achieved weight loss. No significant differences between groups in renal function were observed.In this study we demonstrate that a high protein diet with emphasis on plant source protein vs. a standard diet is feasible in insulin-treated type-2 diabetic patients and reduces insulin requirement and body weight and improves metabolic parameters up to 12 weeks. A high protein diet can thus be considered as an appropriate diet choice for type-2 diabetic patients.
Keywords: diabetes; alimentation; obesity